Using Bioactive Glasses in the Management of Burns - Kargozar, Saeid; Mozafari, Masoud; Hamzehlou, Sepideh; Baino, Francesco (Frontiers in Bioengineering and Biotechnology, 2019)
Abstract The management of burn injuries is considered an unmet clinical need and, to date, no fully satisfactory solution exists to this problem. This study aims to explore the potential of bioactive glasses (BGs) for burn care due to the therapeutic effects of their ionic dissolution products. BGs have been studied for more than 40 years and boast a long successful history in the substitution of damaged tissues, especially bone. Considering their exceptional versatility and attractive characteristics, these synthetic materials have also recently been proposed in the treatment of soft tissue-related disorders such as skin wounds. Specifically, improving fibroblast proliferation, inducing angiogenesis, and eliciting antibacterial activity (with the additional advantage of avoiding administration of antibiotics) are all considered as key added values carried by BGs in the treatment of burn injuries. However, there are some issues that deserve careful consideration while proceeding with the research, including the selection of suitable BG compositions, appropriate forms of application (e.g., BG fibers, ointments or composite patches), as well as the procedures for reliable in vivo testing.